Janus kinase inhibitors in rheumatoid arthritis-associated interstitial lung disease: where do we stand and what may be the future? - Beatrice Maranini; Roberta Foti; Moustapha Taha; Veronica Venturelli; Andrea Lo Monaco; Marcello Govoni (Reumatismo)
Objective. Interstitial lung disease (ILD) is rare, but it is one of the most frequent extra-articular manifestations and a relevant cause of morbidity and mortality in rheumatoid arthritis (RA). Over the past few years, Janus kinase inhibitors (JAKis) have been reported to have promising efficacy in the treatment of active RA, but recent concerns have been raised about their safety profile, namely malignancy and cardiovascular disease, limiting their use to certain patient categories.